Uncertain data: Forms, Semantics, Processing Queries / Trieu Minh Nhut Le, Thanh Ngoc Thi Nguyen, and Dung Hoang Thi Ngoc - Trieu, Minh Nhut Le; Thanh, Ngoc Thi Nguyen; Dung, Hoang Thi Ng (Universiti Teknologi MARA, Selangor, 2020)
Data discovery is a broad discipline that comprises a various of techniques for extracting meaningful information. In practical, there are various reasons for uncertain data such as error devices of data collection, data transferring in interference environment, statistic or survey data, predict information and so on. Therefore, studying and discovering meaningful information on uncertain data have been more challenges. Some researches have been studied definitions and methods for uncertain data to solve specified scenarios according to satisfying criteria on semantics. In this paper, we first review and classify types of uncertain data in specific scenario. Secondly, some cases of queries processing to demonstrate the semantics on uncertain data are analysed based on their answers. Thirdly, we review almost probabilities of queries that has been used to evaluate the performing queries process according to semantics of uncertain. Lastly, we mention some problems of semantics and their answers which have been argued in doing uncertain data research.